The Effect of an Educational Program Based on Behavioral Intention Model on Childbearing in Women During the Covid 19 Pandemic - Somayeh Seifi; Shahnaz Kohan; Zahra Boroumandfar (Iranian Journal of Nursing and Midwifery Research)
Background: Currently, fertility and childbearing rates in Iran are below the replacement level (1.2 children), and Iranian families have a low propensity to have children. The COVID-19 pandemic will also have a negative impact on the decision of couples to have children. The present study was conducted with the aim of investigating the effectiveness of an educational program on women’s childbearing intention under the conditions of the COVID-19 pandemic. Materials and Methods: This study was a clinical trial with a pretest–posttest design, conducted on 80 women (control group = 40 and intervention group = 40) in comprehensive health centers in 2019. The educational program was delivered to the intervention group in 3 sessions. The data collection tools included the Attitudes to Fertility and Childbearing Scale (AFCS), Demographic Information Questionnaire, and researcher-made fertility intention questionnaire. Data were analyzed using t-test, Mann–Whitney, Chi-square test, ANOVA, Bonferroni post hoc test, and Wilcoxon test. Results: The women in the intervention group were in the age range of 18 to 44 years and in the control group were in the age range of 19 to 44 years. The results showed that the mean scores of attitude toward fertility and intention to have children after training were significantly different between the two groups. However, after the training, it was significantly higher in the intervention group than in the control group (F1,67 = 1037, p < 0.001). Conclusions: It seems that the implementation of the use of theoretical models can be effective in the informed decision of families, especially women, for childbearing.